2017
DOI: 10.1103/physrevlett.118.213001
|View full text |Cite
|
Sign up to set email alerts
|

Subfemtosecond Control of Molecular Fragmentation by Hard X-Ray Photons

Abstract: Tuning hard x-ray excitation energy along Cl 1s→σ^{*} resonance in gaseous HCl allows manipulating molecular fragmentation in the course of the induced multistep ultrafast dissociation. The observations are supported by theoretical modeling, which shows a strong interplay between the topology of the potential energy curves, involved in the Auger cascades, and the so-called core-hole clock, which determines the time spent by the system in the very first step. The asymmetric profile of the fragmentation ratios r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
(42 reference statements)
0
30
0
Order By: Relevance
“…the resolving power E/ΔE higher than 5000 (where E is the kinetic energy of electron and ΔE the instrumental resolution), are quite scarce. Up to now, the GALAXIES beamline at the SOLEIL synchrotron [2,3] has been the only facility for high-resolution HAXPES experiments on atomic and molecular science and has been achieving significant results on double-core-hole spectroscopy [4][5][6][7], recoil effects [8][9][10], ultrafast phenomena [11][12][13], post-collision interaction (PCI) [14,15], resonant Auger processes [16][17][18][19][20], and very recent studies on aqueous solution [21,22]. The experiments at the GALAXIES beamline, however, are limited to the excitation energy ranging between 2.3 and 12 keV, while experiments with much higher photon energy are quite scarce.…”
Section: Introductionmentioning
confidence: 99%
“…the resolving power E/ΔE higher than 5000 (where E is the kinetic energy of electron and ΔE the instrumental resolution), are quite scarce. Up to now, the GALAXIES beamline at the SOLEIL synchrotron [2,3] has been the only facility for high-resolution HAXPES experiments on atomic and molecular science and has been achieving significant results on double-core-hole spectroscopy [4][5][6][7], recoil effects [8][9][10], ultrafast phenomena [11][12][13], post-collision interaction (PCI) [14,15], resonant Auger processes [16][17][18][19][20], and very recent studies on aqueous solution [21,22]. The experiments at the GALAXIES beamline, however, are limited to the excitation energy ranging between 2.3 and 12 keV, while experiments with much higher photon energy are quite scarce.…”
Section: Introductionmentioning
confidence: 99%
“…As the probability of radiative relaxation of core-excited atoms increases with atomic number, both RIXS and RAS become equally relevant in the hard x-ray regime [5][6][7][8][9][10][11][12][13][14]. However, the major difference between these techniques appears in the electronic final states reached upon relaxation.…”
mentioning
confidence: 98%
“…The observed narrowing effect occurs in CH 3 I at times significantly exceeding the determined 0.6 fs lifetime of the DCH state, when the population of this state is considerably depleted due to the Auger decay. However, it may play a role in molecules with light atomic constituents such as hydrogen halides undergoing fast dissociation [14].…”
mentioning
confidence: 99%
“…More specifically, Marchenko et al 22 obtained the topology of the potential energy surface (PES) and the lifetime of the DCH states of CH 3 I, by performing complementary measurements of resonant inelastic X-ray scattering (RIXS) and resonant Auger spectroscopy (RAS). Furthermore, the highly repulsive nature of DCH states leading to ultrafast dissociation has been illustrated by Travnikova et al 23,24 Finally, as was demonstrated by Céolin et al, 25 resonant energy transfer (RET) in SF 6 , due to the fill of an initial S 1s −1 vacancy by a S 2p electron, can lead to the formation of S 2p −1 F 1s −1 ts-DCH continuum states.…”
Section: Introductionmentioning
confidence: 87%